Coping Strategy of Student Households in Fulfilling Nutrition During Covid-19 Pandemic - Dewi Rahayu; Dinda Resty Rizana (Poltekkes Kemenkes Riau, 2023)
Malnutrition (Wasting,Stunting) caused by inadequate food intake. Household food security is needed to ensure food fulfillment. Household food security can be seen from the income aspect. The purpose of this study was to observe the coping strategy practices of the households of students majoring in the nutrition of Poltekkes Kemenkes Riau during the Covid-19 pandemic. This type of research is qualitative research and observational. There are 69 research respondents and was determined by simple random sampling. Household food security was explored using the RCSI (Reduced Coping Strategy Index) questionnaire. The results of the study revealed that therespondents used combined coping strategy practices and most frequently used by households is reducing expensive food by 31 respondents and buying ready-to-eat food by 52 respondents. Whereas 1 respondents were rarely or not to eating days (<1x/week) as the last coping strategy.